Correction: Establishment of a Cre-rat resource for creating conditional and physiological relevant models of human diseases - Huimin Zhang; Qi Zheng; Ruby Yanru Chen-Tsai (Transgenic Research, 2026)

Establishment of a Cre-rat resource for creating conditional and physiological relevant models of human diseases - Huimin Zhang; Qi Zheng; Ruby Yanru Chen-Tsai (Transgenic Research, 2021)
The goal of this study is to establish a Cre/loxP rat resource for conditional and physiologically predictive rat models of human diseases. The laboratory rat ( R . norvegicus ) is a central experimental animal in several fields of biomedical research, such as cardiovascular diseases, aging, infectious diseases, autoimmunity, cancer models, transplantation biology, inflammation, cancer risk assessment, industrial toxicology, pharmacology, behavioral and addiction studies, and neurobiology. Up till recently, the ability of creating genetically modified rats has been limited compared to that in the mouse mainly due to lack of genetic manipulation tools and technologies in the rat. Recent advances in nucleases, such as CRISPR/Cas9 (clustered regularly-interspaced short palindromic repeats/CRISPR associated protein 9), as well as TARGATT™ integrase system enables fast, efficient and site-specific introduction of exogenous genetic elements into the rat genome. Here, we report the generation of a collection of tissue-specific, inducible transgenic Cre rats as tool models using TARGATT™, CRISPR/Cas9 and random transgenic approach. More specifically, we generated Cre driver rat models that allow controlled gene expression or knockout (conditional models) both temporally and spatially through the Cre-ERT2/loxP system. A total of 10 Cre rat lines and one Cre reporter/test line were generated, including eight (8) Cre lines for neural specific and two (2) lines for cardiovascular specific Cre expression. All of these lines have been deposited with the Rat Resource and Research Center and provide a much-needed resource for the bio-medical community who employ rat models for their studies of human diseases.

Genome editing in livestock: Are we ready for a revolution in animal breeding industry? - Jinxue Ruan; Jie Xu; Ruby Yanru Chen-Tsai; Kui Li (Transgenic Research, 2017)